Validity and Reliability of WHO Disability Assessment Schedule 2.0 (WHODAS 2.0) Type 12 Questions Indonesian Version on Back Pain - Rijanti, Kusumawardhany Airlangga; Subadi, Imam; Kurniawati, Patricia Maria (Folia Medica Indonesiana, 2021)
The study was to prove the validity and reliability of the WHODAS 2.0 Indonesian version questionnaire in patients with back pain. This study was an observational cross-sectional study conducted in 2018. The study included the filling of WHODAS 2.0 Indonesian version, Indonesian version of Oswestry Disability Index (ODI) questionnaire, Wong-Baker Scale, conducted at Department of Rehabilitative Medicine, Dr. Soetomo General Academic Hospital, Surabaya, Indonesia, against 82 respondents with back pain. Each respondent was given informed consent. The validity of the WHODAS 2.0 Indonesian version questionnaire was measured using Pearson's test on the correlation of WHODAS 2.0 Indonesian version questionnaire and Oswestry Disability Index questionnaire with r >0.3 (0.862). WHODAS 2.0 Indonesian version questionnaire and Wong-Baker Scale had r >0.3 (0.449–0.785). The reliability of the WHODAS 2.0 Indonesian version questionnaire was measured using Pearson's correlation test with r >0.3 (0.764–0.866). WHODAS 2.0 Indonesian version's internal reliability was tested using Cronbach-Alfa Test with alpha >0.6 (0.634–, 853). In conclusion, the WHODAS 2.0 - Indonesian version is a valid and reliable questionnaire for patients with back pain.